Rola kasy rolniczego ubezpieczenia społecznego (KRUS) w wydatkach budżetowych na sektor rolno-żywnościowy w Polsce : dylemat polityki rolnej - Czyżewski, Andrzej; Henisz-Matuszczak, Anna (Role of KRUS in Budgetary Expenses for Agricultural-Food Sector in Poland : Dilemma of Rural Policy, 2005)
The purpose of the matter under discussion is the analysis of the budget's acts in the years 1996-2000 in order to estimate the size and structure of the means destined for the realization of the social policy in the agricultural economy, which is realised in this sector through KRUS. One indicates on macroeconomics determinants of KRUS' functioning. Considerations are ended by conclusions which make a diagnosis of past and present situation, and show necessity of a reform of social services for farmers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 129-136